TRANSFER OF TRAINING (ANALISIS PELAKSANAAN TRANSFER OF TRAINING DI BADAN KEPEGAWAIAN DAERAH (BKD) DAERAH ISTIMEWA YOGYAKARTA) - Citra Pandu Ardaneswari (NATAPRAJA, 2016)
The objective of this research is to examine the implementation of transfer of training in regional employees services agency, Yogyakarta special administrative region. the research used descriptive qualitative research methods. Research results show that the implementation of transfer of training in regional employees services agency, fosters the acquisition of knowledge, both during training exercise and from working colleagues. Employees of the regional employees services agency implement knowledge that they acquire during training that entails takes theories and practices as well as in modifying the implementation of core task and functions. This research found significant influence, include a) internal factors that comprise facilities, leadership support and working colleagues, and reward and punishment; b) external factors that comprise central government policy that by and large, is not commensurate with those implemented at local government level, and technology.Keywords: human resource development, Transfer of Training